Fijian Veterinarian and Para-Veterinarians' Behavior, Attitude and Knowledge Toward Antimicrobial Use and Antimicrobial Resistance: A Qualitative Study - Khan, Xavier; Lim, Rosemary H. M.; Rymer, Caroline; Ray, Partha (Frontiers in Veterinary Science, 2022)
Antimicrobial resistance (AMR) is a global health issue affecting humans and livestock. Reduction in antimicrobial use (AMU) and appropriate use of antimicrobials in livestock production systems have been encouraged. Lack of access to qualified veterinarians, policies regulating AMU and knowledge of AMU and AMR have been identified as drivers of inappropriate AMU behaviour in developing countries. Hence, para-veterinarians take a lead role in providing veterinary services to livestock farmers in developing countries. Our previous work found Fijian farmers lack knowledge and understanding of AMU and AMR. However, the attitude, knowledge, and behaviour of Fijian veterinary professionals towards AMU and AMR is currently unknown. Therefore, this qualitative study used face-to-face, semi-structured interviews to explore and understand Fijian veterinarian and para-veterinarians' attitude, knowledge, and behaviour towards AMU and AMR. A sample of at least ten participants was targeted and recruited from the Central and Western divisions of Viti Levu, Fiji. The Theory of Planned Behaviour (TPB) informed the development of the semi-structured interview guide. Audio-recorded interviews were analysed using reflexive thematic analysis and deductively using TPB. Three key themes were generated: 1) Antimicrobials prescribed and used based on availability and cost rather than clinical need, 2) Para-veterinarians awareness and knowledge of AMR influence treatment decisions, and 3) Limited resources impede effective consultation and veterinary service delivery. This study demonstrated para-veterinarians lacked knowledge and understanding of AMU and AMR. The availability and cost of antimicrobials rather than clinical justification drove antimicrobial prescribing amongst the para-veterinarians. Veterinarians did not visit farms to provide veterinary services; therefore, para-veterinarians provided the veterinary services to the livestock farmers. Lack of human resources, antimicrobials, and physical resources incapacitated veterinary service delivery, where services to farmers’ were delayed or not provided at all. Terms of reference for veterinary service delivery and para-veterinarian training framework targeting prescribing, dispensing, use of antimicrobials and risks associated with inappropriate AMU are recommended as part of antimicrobial stewardship (AMS) programmes. Allocation of physical and human resources to Fijian veterinary services should be considered part of AMS programmes to improve veterinary service delivery to livestock farmers and optimise the AMU at the country level.